2020
DOI: 10.3390/molecules25204861
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Guided Isolation of Acetogenins from Annona cherimola Deciduous Leaves: Production of Nanocarriers to Boost the Bioavailability Properties

Abstract: Annonaceous acetogenins (ACGs) are lipophilic polyketides isolated exclusively from Annonaceae. They are considered to be amongst the most potent antitumor compounds. Nevertheless, their applications are limited by their poor solubility. The isolation of ACGs from Annona cherimola leaves, an agricultural waste, has not been reported to date. Molvizarin (1) cherimolin-1 (2), motrilin (3), annonacin (4) and annonisin (5) are isolated for the first time from A. cherimola deciduous leaves. Annonacin was found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Gutiérrez et al employed SMPMs based on α-CD and urea to encapsulate annonacin. In line with other studies, cytotoxicity to liver cells was the main objective, and it was proven that annonacin is selective to tumor cells, with over 87% of cell survival when the acetogenin is applied to non-tumoral liver cells (HEK-293) [ 20 ]. In this case, although both the encapsulation percentage and the drug delivery time provided the lowest values, it should be highlighted that annonacin is completely different from other previously encapsulated and tested acetogenins, since it presents a mono-THF structure instead of the bis-THF structure of bullatacin.…”
Section: How To Apply Acgs From Annona Cherimola Millmentioning
confidence: 76%
See 4 more Smart Citations
“…Gutiérrez et al employed SMPMs based on α-CD and urea to encapsulate annonacin. In line with other studies, cytotoxicity to liver cells was the main objective, and it was proven that annonacin is selective to tumor cells, with over 87% of cell survival when the acetogenin is applied to non-tumoral liver cells (HEK-293) [ 20 ]. In this case, although both the encapsulation percentage and the drug delivery time provided the lowest values, it should be highlighted that annonacin is completely different from other previously encapsulated and tested acetogenins, since it presents a mono-THF structure instead of the bis-THF structure of bullatacin.…”
Section: How To Apply Acgs From Annona Cherimola Millmentioning
confidence: 76%
“…ACGs have recently generated considerable interest because of the wide range of biological activities that they have exhibited, such as anti-inflammatory, pesticidal, antimicrobial and particularly cytotoxic activities. Several studies have already demonstrated that these compounds present either none or minimal toxicity to normal cells but are highly toxic to cancerous cells [ 20 , 40 , 41 ].…”
Section: Biological Activity and Anticarcinogenic Properties Of The Acgs Isolated From Acmmentioning
confidence: 99%
See 3 more Smart Citations